2012
DOI: 10.4236/ojst.2012.24049
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of salivary tumours at a university teaching hospital in Kenya

Abstract: Salivary gland tumours (SGT) are rare, comprising about 5% of head and neck tumours with a higher incidence reported in the western compared with the African centres. There are few studies on SGTs that have been conducted in Africa. A descriptive retrospective study was done to describe the demographic characteristics, site distribution and histological patterns of SGT at a University teaching hospital in Kenya over a 12-year-duration. There were 132 SGTs out of 2426 biopsies of head and neck tumours, the age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
10
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 25 publications
8
10
3
Order By: Relevance
“…But in our study, the minor salivary glands with 63 (61.2%) cases, was the commonest site of the SGTs that is similar to findings in other studies [6] [21]. A possibility of racial variations existing in the clinico-pathologic distribution of SGTs, with Africans having less proportion of SGTs in the parotid gland, but more proportion occurring in the minor salivary and submandibular glands when compared with white populations in Table 2.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…But in our study, the minor salivary glands with 63 (61.2%) cases, was the commonest site of the SGTs that is similar to findings in other studies [6] [21]. A possibility of racial variations existing in the clinico-pathologic distribution of SGTs, with Africans having less proportion of SGTs in the parotid gland, but more proportion occurring in the minor salivary and submandibular glands when compared with white populations in Table 2.…”
Section: Discussionsupporting
confidence: 78%
“…Poverty, illiteracy, religious faith and low life expectancy may be proffered as some of the reason for the fewer number of elderly SGT patients seen in African studies. Unlike other studies that have reported female preponderance in SGTs [6] [9], our finding was that of male dominance and is similar to the findings of Silas et al [14] in North-Central Nigeria, who attributed this to cultural practices which refuses females from attending hospitals alone without permission from their husbands. In addition however, most women in northern Nigeria are not gainfully employed, and this causes serious problem to the family when it comes to payment of hospital bills.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations